Komunikasi Partisipatif Relawan Pemadam Kebakaran dalam Menanggulangi Kebakaran di Kota Bengkulu - Syafitri, Nabila Nur; Yuliati; Perdana, Dionni Ditya (JURNAL LENSA MUTIARA KOMUNIKASI, 2024)
Fire is a disaster that often occurs in Indonesia, one of the areas that has a fairly high fire rate is Bengkulu City. Therefore, this research is very relevant to find the right solution in improving coordination and quick response in handling fire disasters through community participatory communication in the Volunteer Fire Fighter program. This research aims to analyze how participatory communication is carried out by Firefighter Volunteers in dealing with fires in Bengkulu City. The focus of this research uses the concept of participatory communication which consists of four indicators, namely heteroglasia, dialogic, polyphony and carnival. Using a qualitative approach, this research involved in-depth interviews with several members of the Volunteer Fire Department and the Head of the Prevention Division of the Bengkulu City Fire and Rescue Service. The results of the research show that the participatory communication of the Bengkulu City Fire Brigade Volunteers has gone well, marked by the fulfillment of four important indicators of participatory communication, namely heteroglasia, dialogue, polyphony and carnival. The presence of Bengkulu City Volunteer Fire Fighters with good participatory communication has also increased the speed of response in handling fires. Apart from that, solid cooperation between members of the Volunteer Fire Department and the Government and the Bengkulu City Fire and Rescue Service also increases the effectiveness of fighting fires. This research concludes that participatory communication from Volunteer Firefighters has great potential in increasing the effectiveness of fire management in Bengkulu City, but needs to be supported by a better government role.